Smart Benefits Distribution : Leveraging IoT and Data Analytics for Streamlined Office Efficiency - Venkatarama Reddy Kommidi,; Srikanth Padakanti,; Rajesh Kumar Srirangam, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the transformative potential of integrating Internet of Things (IoT) devices and advanced data mining techniques in benefits distribution systems. Faced with challenges such as long wait times, inefficient processes, and resource mismanagement, government agencies and private organizations are turning to these technologies to revolutionize service delivery. The article discusses how IoT-enabled smart kiosks, occupancy sensors, and process automation tools can streamline operations and improve client experiences. It further examines how data mining techniques, including predictive analytics, clustering, and anomaly detection, can enhance decision-making and operational efficiency. Through a case study and analysis of benefits and challenges, the article demonstrates how this integrated approach can lead to reduced wait times, improved staff productivity, enhanced fraud detection, and significant cost savings, ultimately transforming the landscape of benefits distribution to be more efficient, responsive, and beneficiary-centric.
Keywords: Internet of Things; Data Mining; Benefits Distribution; Digital Transformation; Public Services Efficiency